2002
DOI: 10.1023/a:1013315110746
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Calystegines are nortropane alkaloids that are found in Solanaceae containing the classical tropane alkaloids hyoscyamine and scopolamine, and in other Solanaceae such as potato, Solanum tuberosum (L.). Calystegines are assumed to derive from the classical tropane alkaloid pathway. We isolated a cDNA from S. tuberosum with high homology to the pseudotropine-forming tropinone reductase (TRII), which presents as the first putative metabolite specific to calystegines. The equivalent amino acid sequence shows typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…For two features on the array, a maximum of 5 QTLs were identified. One shows strong homology to a tropinone reductase II (TRII; EST cSTB29M16TH ) [26] involved in the biosynthesis of tropane alkaloids which is known to be expressed in both below- and above-ground potato tissues. The second feature (BF_LBCHXXXX_0032H04_T3M.SCF) with 5 different QTLs has no significant homology to any protein present in the databases nor was its gene structure predicted in the current release of the potato genome annotation [25].…”
Section: Resultsmentioning
confidence: 99%
“…For two features on the array, a maximum of 5 QTLs were identified. One shows strong homology to a tropinone reductase II (TRII; EST cSTB29M16TH ) [26] involved in the biosynthesis of tropane alkaloids which is known to be expressed in both below- and above-ground potato tissues. The second feature (BF_LBCHXXXX_0032H04_T3M.SCF) with 5 different QTLs has no significant homology to any protein present in the databases nor was its gene structure predicted in the current release of the potato genome annotation [25].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that overexpression of the TRI gene can considerably enhance the production of tropane alkaloids in the root cultures of Atropa belladonna [4]. A TRII cDNA that does not accumulate the classical tropane alkaloids was also cloned from potato [9]. TRs are members of a short-chain dehydrogenase family with TR-homologous genes represented in plant species (e.g.…”
Section: Scheme 1 the Tropane-alkaloid Biosynthesis Pathwaymentioning
confidence: 99%
“…TRs are members of a short‐chain dehydrogenase family with TR‐homologous genes represented in plant species (e.g. Arabidopsis thaliana , Solanum tuberosum , Cochlearia officinalis ) that do not produce tropane alkaloids, suggesting that these enzymes may function in otherwise unrelated metabolic pathways [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Tropinone is considered the key intermediate in the biosynthesis of tropane esters in Solanaceous plants. Reduction of tropinone results in the formation of either tropine or its stereoisomer pseudotropine, and is catalysed by tropinone reductase I, TRI (EC 1.1.1.206) and tropinone reductase II, TRII (EC 1.1.1.236), respectively [42][43][44]. The former is the precursor of most clinically used tropane esters, whereas the latter is an intermediate in the formation of some rarer esters (e.g.…”
Section: Nicotine Alkaloids Are Biosynthetically Linked To Tropane Almentioning
confidence: 99%